Increase of Silica Recovery by Lignocellulose-degrading Enzyme Complex from Cow Rumen Fluid in a Reactive Extraction of Oryza sativa L. Husk - Robert Manurung; Muhammad Rizki Fajar Ilhamy; Khairul Hadi Burhan (3BIO: Journal of Biological Science, Technology and Management, 2020)
Silica is one of the beneficial nutrients and has various essential roles to cope with stresses situation in the graminaceous plant. The availability of Si on earth is abundant however the form that can be readily uptake by the plant is limited, and without external addition, the silica content in the cultivated land would be depleted and decreasing plant growth, recycle Si from the decaying plant is a better alternative to protect from that situation. Rice husk is a leftover paddy by-product having significant Si content that can be reused. This study offered a biological way to treat the rice husk using rumen fluid as a better alternative to the high energy consuming thermal procedure. Rice husk was macerated in rumen fluid, the kinetic and model of lignocellulose degradation were evaluated. The study in Si release in liquid media i.e. 0.05 M hydrochloric acid, 0.1 citric acid and aquades, and Si extraction in alkaline solution 1 M KOH using the rumen-treated husk showed that this method could be a better alternative to develop high Si content of solid and liquid fertilizer, respectively.